Correlation analysis on sensory characteristics and physicochemical indices of bone broth under different processing methods. (October 2022) - Li, Xiangyuan; Meng, Hengli; Zhu, Yiwen; Shu, Shumin; Bao, Yugang; Jiang, Shui; Liu, Yuan
Highlights: The taste of bone broth with different processing could be distinguished by e-tongue. Quantitative descriptive analysis was used to evaluate bone broth's sensory profile. Different ratio of marrow-bone to mixed-bone broth showed different taste preference. Odor, flavor and umami taste correlated significantly with quality indices. Abstract: Understanding the taste is the key for optimizing the palatability of bone broth rich in flavor and nutrition. This study revealed the taste profile of bone broth under different processing methods including cooking time, temperature, bone freshness and ratio of marrow-bone to mixed-bone. Taste compounds were determined by chemical analysis, taste profile was uncovered by quantitative descriptive analysis (QDA) and correlation analysis was executed. As a result, 5'-AMP (11.43∼52.08 μg/mL), 5'-IMP (3.32∼32.90 μg/mL), umami (22.19∼63.22 μg/mL) and sweet amino acids (36.93∼120.02 μg/mL) were the dominant taste compounds. Cooking temperature affected positively on umami and sweet amino acids content (4.50∼14.69 μg/mL Asp and 5.26∼16.11 μg/mL Ser). Yellowness, turbidity, consistence, meaty, marinated and fatty odors, umami taste and smoothy mouth-feel were the key indicators among bone broths with different bone ratios and had a strong correlation with physicochemical indices and taste components ( p < 0.05). This study could provide flavor-oriented optimization for home cooking and industrial bone broth products.